2009
DOI: 10.1037/a0016271
|View full text |Cite
|
Sign up to set email alerts
|

Memory operations that support language comprehension: Evidence from verb-phrase ellipsis.

Abstract: Comprehension of verb-phrase ellipsis (VPE) requires reevaluation of recently processed constituents, which often necessitates retrieval of information about the elided constituent from memory. A. E. Martin and B. McElree (2008) argued that representations formed during comprehension are content addressable and that VPE antecedents are retrieved from memory via a cue-dependent direct-access pointer rather than via a search process. This hypothesis was further tested by manipulating the location of interfering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 32 publications
8
77
1
Order By: Relevance
“…Chapman & colleagues (2002) and Michael et al (2012) have previously reported on the relationship between syntactic comprehension ability and memory in people with DS. Given our specific focus on complex sentences, which require the processing and integration of information from two clauses ( Martin & McElree, 2009), it is not surprising that we find memory to play an important role. More surprising was the independent contribution of DS status over and above poor memory skills, which indicates that the language difficulties of children with DS go beyond those usually associated with limited memory and nonverbal ability.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Chapman & colleagues (2002) and Michael et al (2012) have previously reported on the relationship between syntactic comprehension ability and memory in people with DS. Given our specific focus on complex sentences, which require the processing and integration of information from two clauses ( Martin & McElree, 2009), it is not surprising that we find memory to play an important role. More surprising was the independent contribution of DS status over and above poor memory skills, which indicates that the language difficulties of children with DS go beyond those usually associated with limited memory and nonverbal ability.…”
Section: Discussionmentioning
confidence: 95%
“…Because the current study focuses particularly on complex sentences, and these constructions require the parsing of different clauses over a more lengthy time span ( Martin & McElree, 2009; Marton et al , 2006), we might predict that short term and working memory would be particularly relevant to the ability of someone with DS to understand them. However, to our knowledge, this has never been investigated in relation to this population.…”
Section: Introductionmentioning
confidence: 99%
“…However, when a WM load displaces information from focus, that displaced lexical information must be re-retrieved at which point it is subject to interference both from items currently in focus as well as from other cue-relevant information (cf. Badecker & Kuminiak, 2007; Fedorenko, Gibson, & Rohde, 2006; Gordon, Hendrick, & Levine, 2002; Lewis & Vasishth, 2005; A. Martin & McElree, 2009; Van Dyke, 2007; Wagers, Lau, & Phillips, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…MR-SAT is an attractive technique to use in studying language comprehension because it dissociates processing speed from processing accuracy (McElree, 2000; McElree et al, 2003; Foraker and McElree, 2007; Martin and McElree, 2008, 2009, 2011). In a MR-SAT paradigm, participants are required to make acceptability judgments at pre-specified response latencies.…”
Section: Methodsmentioning
confidence: 99%